Does Co-Residence with Parents-In-Law Reduce Women's Employment in India? - Rajshri Jayaraman; Bisma Khan (Center for Economic Studies and ifo Institute (CESifo), 2023)
We examine the effect of co-residence with fathers- and mothers-in-law on married women's employment in India. Instrumental variable fixed effects estimates using two different household panel datasets indicate that co-residence with a father-in-law reduces married women's employment by 11-13%, while co-residence with a mother-in-law has no effect. Difference-in-difference estimates show that married women's employment increases following the death of a co-residing father-in-law, but not mother-in-law. We investigate three classes of explanations for this: income effects, increased domestic responsibilities, and social norms. Our evidence is consistent with gender- and generational norms intersecting to constrain married women's employment when parents-in-law co-reside.
Keywords: J16; J22; J12; O12; Z13; 330; female employment; family structure; labour supply; parents-in-law